2023
DOI: 10.1136/bmjopen-2022-065714
|View full text |Cite
|
Sign up to set email alerts
|

Association between attending cultural events and all-cause mortality: a longitudinal study with three measurements (1982–2017)

Abstract: ObjectivesTo examine the association between cultural attendance and all-cause mortality.DesignA longitudinal cohort study over 36 years (1982–2017) with three 8-year interval measurements of exposure (1982/1983, 1990/1991 and 1998/1999) to cultural attendance and a follow-up period to 31 December 2017.SettingSweden.ParticipantsThe study included 3311 randomly selected individuals from the Swedish population with complete data for all three measurements.Primary outcome measurementsAll-cause mortality during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(60 reference statements)
2
0
0
Order By: Relevance
“…The main strengths were the approach of using both MSM-Cox with IPW together with Cox proportional hazard regression models on longitudinal data including three measurements during a follow-up of 36 years in both men and women. Furthermore, the findings of an association between cultural exposure and CHD were in-line with previous findings on mortality from more traditional epidemiological design 5 8 . The consistency of our results with those from other studies further supports the validity and robustness of our findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The main strengths were the approach of using both MSM-Cox with IPW together with Cox proportional hazard regression models on longitudinal data including three measurements during a follow-up of 36 years in both men and women. Furthermore, the findings of an association between cultural exposure and CHD were in-line with previous findings on mortality from more traditional epidemiological design 5 8 . The consistency of our results with those from other studies further supports the validity and robustness of our findings.…”
Section: Discussionsupporting
confidence: 89%
“…In psychology, the evidence on leisure’s strengthening effect on health has been accumulating 3 and animal trials have found an enriched environment to be associated with learning and health in mice 2 , 4 . In medicine, attendance at fine arts events was found to be inversely associated with all-cause mortality by our group over two decades ago 5 , which has been replicated in several studies over the intervening years 6 8 . However, the potentially causal relationship between cultural activities and the most common causes of mortality 9 , 10 has not yet been established.…”
Section: Introductionsupporting
confidence: 74%